2020
DOI: 10.15537/smj.2020.2.24841
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and imposter syndrome among Saudi young adults

Abstract: Objectives: To determine the prevalence of imposter syndrome (IS) among Saudi adults and its association with burnout. Methods: Using non-probability convenience sampling, we carried out a cross-sectional analytical study among adults in Northern Saudi Arabia. Data collection toll was a self-administered questionnaire containing young imposter scale (YIS), Maslach burnout inventory (MBI) and depression, anxiety, and stress scale 21 (DASS 21). These 3 scales are valid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…For example, in a study of IP and career development, Neureiter and Traut‐Mattausch (2016a) found that IP led to a decreased motivation to lead. Alrayyes et al (2020) found a positive relationship between IP and stress. Further, Rohrmann et al (2016) found that managers who experienced IP reported being more stressed and strained by their work.…”
Section: Resultsmentioning
confidence: 97%
“…For example, in a study of IP and career development, Neureiter and Traut‐Mattausch (2016a) found that IP led to a decreased motivation to lead. Alrayyes et al (2020) found a positive relationship between IP and stress. Further, Rohrmann et al (2016) found that managers who experienced IP reported being more stressed and strained by their work.…”
Section: Resultsmentioning
confidence: 97%
“…It may be hypothesized that implications of these findings could impact academic or professional success, job satisfaction, self-efficacy, work engagement, and/or propensity for burnout as individuals may work harder to "prove themselves" due to having fraudulent feelings. 19,20 However, evidence of such associations would need to be investigated and documented to draw definitive conclusions. It also may be interesting to explore how IP feelings change throughout one's academic or professional career as well as what demographic or environmental factors correlate with IP results.…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 0 to 30, with higher scores indicating a higher SE. A cut-off value of <16 was used to define an individual as having low SE [ 33 ].…”
Section: Methodsmentioning
confidence: 99%